THU0063 Outcomes of Treat-To-Target Strategy in Established Rheumatoid Arthritis: A Long-Term Prospective Cohort Study. (15th July 2016) - Andrade, N.P.B.D.; Chakr, R.M.D.S.; Xavier, R.M.; Viecceli, D.; Correa, R.; Oliveira Filho, C.M.; Brenol, C.V.
Abstract : Background: Treating rheumatoid arthritis (RA) to a target has become a landmark strategy to be pursued in every patient. Compared to usual care, treat to target (T2T) has decreased radiographic progression and improved quality of life and physical function 1 . Nonetheless, few studies have addressed the true long-term impact of a T2T strategy in a real-world setting with established RA patients 2, 3 . Objectives: To examine the long-term effectiveness of a treat-to-target strategy in patients with established rheumatoid arthritis in daily practice. Methods: Rheumatoid arthritis patients previously treated under usual care condition were started on a T2T strategy between March 2005 and February 2007 and followed through December 2014. Participants were seen every 3 months until remission/low disease activity was reached and every 6 months afterwards. After DMARD change, participants were assessed monthly for three consecutive months. Treatment escalation followed a step-up strategy, according to national recommendations. Disease activity was measured by DAS28 and CDAI, and physical function by HAQ. Data were extracted by standardized chart and research forms review. Change in disease activity and physical function was compared using Wilcoxon's test and Generalized estimate equations. Results: Significant improvements were seen in both composite scores during follow-up period. There was a significant reduction in DAS28 (4.6±0.1 vs. 3.1±0.1; p<0.001) and in CDAI (21.2±1.0 vs. 7.9±0.7; p<0.001). Physical function also improved, as demonstrated by reduction in HAQ-DI (1.3±0.05 vs 1.0±0.1; p<0.001). The reduction in DAS28, CDAI and HAQ-DI was nonlinear. The percentage of participants in remission increased significantly from 11% to 35% by DAS28 and from 6% to 19% by CDAI (p<0.001). Likewise, there was an improvement in LDA from 10% to 28% by DAS28 and from 22% to 52% by CDAI (p≤0.001). At the end of follow up, 62% of the cohort achieved the target by DAS28 and 71% by CDAI. As well as 30% of participants reached HAQ≤0.5 and DAS≤3.2. Conclusions: Treat-to-target strategy aiming for remission or low activity disease is effective in patients with established RA. The access to biologic DMARDs might have contributed to achieve disease activity control in a substantial proportion of the patients. References: Grigor C, Capell H, Stirling A, McMahon AD, Lock P, Vallance R, et al. Effect of a treatment strategy of tight control for rheumatoid arthritis (the TICORA study): A single-blind randomised controlled trial. Lancet. 2004;364:263–9. Fransen J, Moens HB, Speyer I, van Riel PLCM. Effectiveness of systematic monitoring of rheumatoid arthritis disease activity in daily practice: a multicentre, cluster randomised controlled trial. Ann Rheum Dis. 2005;64:1294–8. Pope JE, Haraoui B, Rampakakis E, Psaradellis E, Thorne C, Sampalis JS. Treating to a Target in Established Active Rheumatoid Arthritis Patients Receiving a Tumor Necrosis Factor Inhibitor: Results From a Real-World Cluster-Randomized Adalimumab Trial. Arthritis Care Res. 2013;65(9):1401–9. Disclosure of Interest: None declared